Dental Erosion Prevalence and Risk Factor in Hypersensitive Patients - Abdul S. T. Ali; Farah Z. Alhamdan; Farah T. Thabet; Norah K. Alsuwaidan; Rahaf M. Almontashri; Reem M. Alanazi (Journal of Pharmacy and Bioallied Sciences)
Introduction: Dental erosion is common, and patient ignorance is a major issue. Extrinsic and intrinsic factors affect erosion. Some recommend evaluating and treating erosion patients following a brief review of the causes. These involve a comprehensive evaluation of the condition and medical history to identify risk factors for further tooth deterioration. To prevent further degeneration, immediate restorative therapy is needed. Materials and Methods: A cross-sectional questionnaire was given to Kerala Dental Clinic patients with dentinal hypersensitivity (DH). A total of 5 random clinics from 14 Kerala districts were chosen. At least a total of 1848 of 3500 patients responded. During the COVID-19 epidemic, an online semistructured survey was created using Google Forms to collect data. The current isolation approach discourages large gatherings and face-to-face contact. Google Forms were used to seek informed consent before filling out the questionnaire. Self-administered 20 questions were used to gather information regarding oral hygiene, bad habits, food, and eating disorders, and we inquired whether subjects ate acidic meals and drinks. Results: Most persons with dentine hypersensitivity eat packaged food (70%), pickles (62%), soft drinks (58%), and sweets (56%). Dental erosion is also linked to alcohol consumption (40.4%), teeth clenching (37.4%), mouth breathing (16.4%), and gum chewing (27.5%). Mouthwash-using DH patients (55%) had tooth disintegration.